(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background : Meconium Ileus (MI) accounting for 9–33% of neonatal intestinal obstruction and one of the common cause of intestinal obstruction in neonate. Near about 50% can be present with various complications. Options for surgical management of MI include resection of dilated ileum with primary anastomosis, Bishop–Koop ileostomy, Santulli procedure or Mikulicz procedure and T tube ileostomy. In our center, before January 2015, mostly Mikulicz and few Bishop- Koop procedures were done for MI. But, the complications were high. From 2015, we started to perform T tube ileostomy and Bishop-Koop procedure in simple MI. In complicated cases Mikulicz and Bishop-Koop procedure were done and the scenario changed. This study was done to compare the outcome of MI surgery before and after January 2015. Methods: This was a retrospective study done in our center during January 2011 to December, 2016 (5 years). All cases were divided into two groups (Group-A: January 2011 to December 2014 and in Group-B: January 2015 to December 2016). Demographic data and surgical outcomes were compared. Results: Total 216 cases were included, in Group-A: 123 patients and others were in Group- B. Simple MI were 49% in Group-A and 56% were in Group-B. Complicated MI presented with small gut volvulus (43.3%) gangrene of loaded ileum (32.2%) perforation with peritonitis (37.8%) intestinal atresia with adhesions (16.3%) and meconium pseudocysts in 12 cases (16%). 11 patients had more than one complication. All the postoperative complications were found significantly high in Group-A except anastomotic leakage. Mortality was also significantly high in Group-A. Conclusion: Morbidity and mortality were significantly reduced with increasing practice of T tube ileostomy and Bishop-Koop procedure in simple and complicated Meconium ileus. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 5-8